Lean Management Beyond Manufacturing A Holistic Approach - Bhasin, Sanjay (Springer International Publishing : Imprint: Springer, 2015)
Exploring Lean manufacturing in a holistic manner, this book helps organizations to implement Lean principles successfully by offering theoretical, empirical and practical knowledge. It empirically demonstrates how a successful Lean initiative can improve organizational efficiency, and incorporates valuable primary research to substantiate findings. It argues that Lean principles need to be applied throughout the value chain in order to be successful , and suggests that these tools need to be aligned with culture and change management. Chapters examine issues including Lean cultures, impediments to Lean, Lean and performance measurement, and the impact of Lean. Viewing Lean as a never-ending journey, this book provides a valuable resource to practising Lean managers, and specialist researchers and students, and also offers an important reference for organizations embarking on their Lean voyage.